(untitled) (African Journal of Biomedical Research, 2020)
Most herbal products are used with prescription drugs and have been found to affect the pharmacokinetics of these prescription drugs. The effect of concurrent administration of Garcinia kola on the pharmacokinetic parameters and penetration profile of rifampicin into the lung tissues were investigated using animal model. Albino rats in group A received rifampicin 10 mg/kg alone orally; Group B and C received 100 mg/kg and 200 mg/kg of Garcinia kola extract respectively for 10 days and on day 11, rifampicin 10 mg/kg was given. Blood samples were withdrawn from each group at 0.5, 1, 2, 4, 8, 12 and 24 h time intervals respectively. Blood samples were also withdrawn from the lungs in each group after 24 h and assayed to determine the concentration of rifampicin in the lungs. Both 100 and 200 mg/kg of Garcinia kola showed reduction in the maximum concentration (Cmax), area under concentration (AUC), clearance time (ClT), and time for plasma concentration to decrease by half (t1/2) of rifampicin. Garcinia kola significantly (P = 0.01) decreased concentration of rifampicin in the lungs by 32% and 39 % respectively. Our results show that the co-administration of Garcinia kola and rifampicin impairs the bioavailability of rifampicin and its penetration into the lungs.